EKSISTENSI PT. RIAU TAXI DI TENGAH ADANYA TRANSPORTASI ONLINE DI KOTA PEKANBARU - Silva Nadia; Swis Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Online transportation is a phenomenon of social change in the field of transportation. The operation of online transportation threatens the existence of PT. Riau Taxi. In order to survive until now, PT. Riau Taxi not only requires material capital but also social capital. The formulation of the problem discussed in this study is how the existence and social capital of a PT. Riau Taxi in the midst of an online transportation in the Pekanbaru City. The theory used in this study is the theory of social capital put forward by Putnam which consists of network, trust and norm. The study used descriptive qualitative research method. The technique of determining the subject in this study used a purposive sampling technique. The subject amounted to 6 people, namely those who were working or who had worked in PT. Riau Taxi at least 1 year. The result of this study indicate that after an online transportation operates, PT. Riau Taxi no longer exists. This is caused by the inequity of regulations between online transportation and PT. Riau Taxi, and PT. Riau Taxi does not carry out renewal and does not prioritize the completeness of the fleet. The social capital formed by PT. Riau Taxi caused the company to survive until now. The network formed makes PT. Riau Taxi able to find out the problems of other taxi companies and find solutions to the problems at hand. The trust formed resulting in PT. Riau Taxi getting regular customers, and being able to maintain the remaining driver. Established norms can prevent disputes between fellow taxi companies and make PT. Riau Taxi and their member directed. Keywords: Existence, Social Capital, PT. Riau Taxi, Online Transportation